Development of filler-free and ambient-cured fly ash based geopolymer brick utilizing low molar concentration of activating solution - Singh S.B.; Maiti P.R.; Mohanty S. (My University, 2025)
In this study, an effort has been undertaken to develop geopolymer bricks (GPB) using fly ash and an activating solution without the addition of any filler material. The primary objective is to establish the optimum mix ratio with the lowest possible concentration of sodium hydroxide (NaOH) in activating solution when mixed with fly ash, resulting in the GPB having compressive strength exceeding 10 MPa and water absorption below 20 % (Class-10 bricks). To achieve this objective, different activating solutions consisting of NaOH, a combination of NaOH and sodium silicate (Na2SiO3), and a combination of NaOH, Na2SiO3, and additional water were used. The samples underwent ambient curing until the age of testing. The X-ray diffraction (XRD), scanning electron microscopy (SEM), and energy dispersive X-ray spectroscopy (EDS) analyses examined the microstructural behavior of the GPB. Experimental results indicated that the compressive strength of 18 MPa and water absorption of 16.49 % was achieved when 2 M NaOH with Na2SiO3 and 5 % extra water were used to activate fly ash. Microstructural analysis revealed that the undissolved fly ash particles served as filler material, while the dissolved fly ash helped in the synthesis of cementitious material. The performance of these bricks was found to be equivalent to that of the traditionally available burnt clay bricks. © 2024 The Authors